Experimental evaluation of anxiolytic and antidepressant activities of methanolic extract of Triticum aestivum (wheatgrass) in albino mice - Saroj Kothari; Ajay Gupta (Journal of Applied Pharmaceutical Research, 2023)
Background: Anxiety and depression are common psychiatric conditions. The present study was carried out to find antianxiety and antidepressant activity of methanolic extract of Triticum aestivum (wheat grass) in mice. Materials and methods: The methanolic extract of Triticum aestivum (META) was screened for antianxiety activity by elevated plus maze (EPM) and light and dark box (LDB) and for antidepressant activity by forced swim test (FST) and tail suspension test (TST) in mice. Animals were divided into four groups having six animals in each group. Group I served as control and received gum acacia aqueous suspension 10 ml/kg, Groups II and III served as test groups and received META 200 and 400 mg/kg, respectively, Group IV served as standard group and received diazepam 1 mg/kg for antianxiety activity and fluoxetine (20 mg/kg) for antidepressant activity once daily for thirty days. Result: META 200 and 400 mg/kg showed significant (P < 0.01) dose-dependent increase in entries and stay in the open arms in EPM and entries and stay in the light compartment in LDB as compared to control. Antianxiety effect of META at dose of 400 mg/kg was comparable (P > 0.05) with diazepam 1mg/kg. META 200 and 400 mg/kg also produced dose-dependent significant (P < 0.01) antidepressant effect, indicated by reduction in the immobility time as compared to control in both FST and TST. The antidepressant activity of META at dose of 400 mg/kg was comparable (P > 0.05) with fluoxetine 20 mg/kg. Conclusion: Results of our study suggested that META possess dose-dependent significant antianxiety and antidepressant activities.